Młodzi literaci wydają "Ziemię Lubuską", czyli wokół jednodniówki z 1955 roku = Young writers publish "Ziemia Lubuska", a one-off magazine from 1955 - Szott, Mirosława (1987- ) (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
"Ziemia Lubuska" is a one-off periodical, whose only issue appeared in 1955 (the hundredth anniversary of the death of Adam Mickiewicz) in Zielona Góra on the initiative of the Young Writers? Association operating at the Regional Board of the Polish Youth Union. Most of its editorial team formed the later "Nadodrze" editorial board. The journal was regarded as heralding the arrival of the post-war literary community created in Zielona Góra, and that is why 1955 is seen as a turning point. In this article the author outlines the context of the creation of the one-offperiodical, discusses its contents and reception, and describes the reasons for not publishing the second issue based on the discussion that took place in "Gazeta Zielonogórska" in 1956.
Keywords: jednodniówka; Koło Młodych Literatów; Ziemia Lubuska (czasapismo); literaci lubuscy; one-off periodical; Young Writers' Circle; Ziemia Lubuska (magazine); Lubusz writers